Fire load, the foundation of fire protection. The case of an animal nutrition and health company - Rodríguez, M. A. (Facultad de Bioquímica y Ciencias Biológicas (UNL), 2021)
Fire load is defined as the weight of wood per unit area (Kg / m2), capable of developing an amount of heat by combustion equivalent to that of the materials contained in the fire sector under study. In this research, the fire load calculation was carried out in facyt SRL, a company dedicated to the production of nutrition and animal health products, where we will find specific materials for its activity, such as raw materials for vitamin nuclei and drugs, in this way It is intended to establish antecedents for future investigations in companies of the same or similar sector. Once the fire load was obtained, the corresponding risk was assigned to the registered fuels and the extinguishing potential for the fire extinguishers was identified, as well as the expected fire resistance for the building's constituent elements. It was determined what kind of extinguishers should be present, the distribution that they should have and both the quantity and the width of exit of the necessary means of escape. Once the calculations were completed, the corresponding conclusions were obtained.